ANALYSIS OF DOMESTIC AND INTERNATIONAL APPROACHES TO THE ADVANCED EDUCATIONAL PRACTICES IN THE ELECTRONIC NETWORK ENVIRONMENT - Tatiana N. Noskova; Tatiana B. Pavlova; Olga V. Yakovleva (National Research Mordova State University, 2016)
Introduction: human activities related to the use of information are being transformed under the influence of computer technology. Variable solutions to information problems are emerging; demands and require¬ments for the competence are changing on the labour market. Educational practices are destined to form a new learning behaviour for the 21st century, adopting lifelong learning strategy. The main purpose of the article is to answer the question as to how to transform existing pedagogical theory and practice under current conditions of electronic environment. Publishing of this article is coherent with concept of the journal Integration of Education, analyzing Russian and world experience in the development of education systems. This approach is important for dissemination and implementation in practice. This article explores the challenges of information technology and technical support of the educational process in universities and schools. The study of these issues is in the field of view of the journa l. Materials and Methods: the paper elaborates on the results of domestic and international educational theory and practice, comparison methods, drawing on student's survey in the framework of international research in the field of e-learning in higher education institutions. Results: the main approaches, applied to the formulation of educational practices in the electronic environ-ment, were analyzed. The most topical national approaches include system, activity, polysubject (dialogical), context, and dialogical ones. Among international approaches self-directed learning, educational communication strategies, experiential learning, training in partnership, collaborative learning, learning in online communities, situational training were analyzed. Specifics of electronic educational interactions with distributed in time and space activities of teachers and students, create the preconditions for the implementation of new educational practices. Educational practices should respond to the rapidly changing labour market request and information behaviour of the "digital" generation. Discussion and Conclusions: educational practices in the digital environment should be subject-centered, with a high degree of interaction, cooperation and teamwork. They should be updated in cognitive, moti-vational and regulatory aspects, in order to enrich the activities of learners through the expansion of the educational objectives range and time-space boundaries. Such educational practices are an important part of the conscious self-development process.